The Influence of Fear of Missing Out (FOMO), Lifestyle and Sharia Financial Literacy on Impulse Buying Sharia Fashion - Febrian Wahyu Wibowo; Baiq Ismiati; Rusny Istiqomah Sujono; Jelena Ika Setiyawati (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2026)
The needs of today's society are very diverse, especially in the sharia fashion industry. In addition to basic needs, the rapidly growing modern phenomenon is driven by psychological and social factors. The development of the sharia fashion industry has given rise to various model trends in society. This raises concerns in consumer behavior, namely impulse buying. This study aims to analyze the effect of Fear of Missing Out (FOMO), lifestyle, and sharia financial literacy on impulse buying sharia fashion. Through a quantitative approach, data were obtained from 130 respondents with the criteria of having an interest in sharia fashion using a purposive sampling technique. The analysis method used is multiple linear regression. The results of the study concluded that Fear of Missing Out (FOMO), lifestyle, and sharia financial literacy on impulse buying sharia fashion simultaneously have a significant effect on purchasing decisions. Partially, Fear of Missing Out (FOMO) and lifestyle have a positive and significant effect, while sharia financial literacy shows a significant negative effect. These findings provide implications for consumers to improve sharia financial literacy in order to control impulse buying behavior caused by FOMO and lifestyle. Kebutuhan masyarakat saat ini sangatlah beragam, khususnya dalam industri sharia fashion. Selain kebutuhan dasar, fenomena modern yang berkembang pesat yang didorong oleh faktor psikologis dan sosial. Berkembangnya industri sharia fashion ini memunculkan berbagai tren model di masyarakat. Hal ini memberikan kekhawatiran dalam perilaku konsumen, yaitu impulse buying. Penelitian ini bertujuan untuk menganalisis pengaruh Fear of Missing Out (FOMO), lifestyle, dan sharia financial literacy terhadap impulse buying sharia fashion. Melalui pendekatan kuantitatif, data diperoleh dari 130 responden dengan kriteria memiliki ketertarikan terhadap sharia fashion dengan menggunakan teknik purposive sampling. Metode analisis yang digunakan adalah regresi linear berganda. Hasil penelitian menyimpulkan bahwa Fear of Missing Out (FOMO), lifestyle, dan sharia financial literacy terhadap impulse buying sharia fashion secara simultan berpengaruh signifikan terhadap keputusan pembelian. Secara parsial, Fear of Missing Out (FOMO) dan lifestyle memiliki pengaruh positif dan signifikan, sedangkan sharia financial literacy menunjukan pengaruh negatif signifikan. Temuan ini memberikan implikasi bagi konsumen untuk meningkatkan literasi keuangan syariah guna mengontrol perilaku impulse buying yang disebabkan oleh FOMO dan lifetsyle.